Therapeutic Practice: Western and Islamic Perspectives - Al-Fathan; Amal Fathullah Zarkasyi; Nur Hadi Ihsan (al-Afkar, Journal For Islamic Studies, 2024)
This chapter explores the concept of Western therapeutic practice which applied to those who experienced jinn possession, evil eye, and witchcraft that caused health problems for human beings. The type of diseases will elaborate from the Western point of view through anthropological and psychiatric perspectives along with the cure or therapy that is given to the patient who suffering from the disease in providing therapeutic healthcare. The researchers found that there is direct relationship between the heart-rhythm patterns and spectral information encoded in the frequency spectra of the magnetic field radiated by heart. The human body is replete with mechanisms for detecting its external environment. Sense organs, the most obvious example, are specifically geared to react to touch, temperature, select ranges of light, sound waves, etc. these organs are acutely sensitive to external stimuli. Every cell in our bodies is bathed in an external and internal environment of fluctuating invisible magnetic forces So, when patient having touch from professional healer (ṭabīb al-rūhī), it will be affected to his organs and help him to get speed recovery from physical disease or mental disorder by the permission of Allah Almighty.